Health related quality of life and its impacts by chronic diseases in urban community population, Shanghai, China in 2015. Issue 8 (14th September 2021) - Chang, Rui; Qian, Xiaolin; Xuan, Zeliang; Xu, Yingsheng; Chen, Yue; Gu, Haiyan; Fu, Chaowei
ABSTRACT: This survey aimed to describe the health-related quality of life (HRQoL) and to explore the relationship between chronic diseases and HRQoL among urban residents in Shanghai, China. A cross-sectional study of 9 426 adults was conducted in Xuhui District of Shanghai, China in 2015. The EuroQol five-dimension three-level (EQ-5D-3 L) was used to measure HRQoL. The average age of subjects was 55.6 ± 17.4 years and 53% were female. Their mean values of utility and visual analogue scale (VAS) were 0.974 ± 0.099 and 80.00 ± 12.36, respectively, which were above the Chinese norm values. Women had lower scores compared with men. The utility value decreased with age, which accelerated after the age of 55 years. Chronic conditions including diabetes, tumor, cardiovascular disease, and respiratory disease, were significantly related to HRQoL, and the reported proportions of problems in the five dimensions increased with the number of chronic diseases (p < 0.05). Chronic diseases except for respiratory disease had a negative effect on HRQoL utility value and VAS score after the adjustment for covariates (p < 0.05). Chronic diseases had a negative impact on both EQ-5D-3 L utility and VAS scores, although the health-related quality of life for the study was above the national average.